2008
DOI: 10.1007/s10811-008-9387-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of algal spore lytic C17 fatty acid from the crustose coralline seaweed Lithophyllum yessoense

Abstract: The algal spore lytic fatty acid of 8,3) was isolated from the crustose coralline seaweed Lithophyllum yessoense. HpDTE, an odd-numbered carbon fatty acid, showed more than 50% lysis at a concentration of 5 μg.mL −1 against the spores of three chlorophyte species, nine rhodophytes, four phaeophytes, and the cells of four phytoplankton species. Lysis activity increased with the number of double bonds and carbon atoms in the fatty acid increased. HpDTE showed a ten-fold stronger activity with a LC 50 of 3.1 μg.m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…In this work, the species was identifi ed as the C. pilulifera using tier numbers, even without reproductive structures and characteristics, but with complementary support of 18S rDNA, psbA, and rbcL gene sequences. Among the factors preventing the settlement or germination of fl eshy seaweed spores, we found that PUFAs have potent lytic activity against algal spores (Luyen et al, 2009). When preparing biomimetic coralline alga material, the antifouling activity could be enhanced by adding bioactive PUFAs.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In this work, the species was identifi ed as the C. pilulifera using tier numbers, even without reproductive structures and characteristics, but with complementary support of 18S rDNA, psbA, and rbcL gene sequences. Among the factors preventing the settlement or germination of fl eshy seaweed spores, we found that PUFAs have potent lytic activity against algal spores (Luyen et al, 2009). When preparing biomimetic coralline alga material, the antifouling activity could be enhanced by adding bioactive PUFAs.…”
Section: Discussionmentioning
confidence: 96%
“…The fatty acids from healthy Corallina pilulifera tissue, 31.4% were ω-3 eicosapentaenoic acid (EPA; C20:5) and 14% were the other PUFAs. In a previous study, EPA showed strong lytic activity against algal spore with LC 50 = 2.1 μg ml -1 (Luyen et al, 2009). Therefore, the preparation of biomimetic calcium carbonate nanoparticles with EPA is suggested to have potent antifouling activity as an environmentally friendly biocontrol.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This focus has shifted attention to alternative seaweed control technologies, such as antifouling or algicidal agent development based on selective natural products. For example, the coralline alga Lithophyllum yessoense produces an algal spore lytic C17 fatty acid (Luyen et al 2009), and the red seaweed Ceramium rubrum has anti-germination activity in Sargassum muticum, Enteromorpha intestinalis, and Ulva lactuca (Hellio et al 2002). The brown seaweed Dictyota dichotoma inhibits the growth of the harmful algal blooming dinoflagellate Ostreopsis cf.…”
Section: T Mehader Getachew Et Almentioning
confidence: 99%